2006
DOI: 10.1016/j.cub.2006.03.057
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro FRAP Identifies the Minimal Requirements for Mad2 Kinetochore Dynamics

Abstract: In vitro FRAP is a widely applicable approach to dissecting the molecular bases of the interaction of a macromolecule with an insoluble cellular scaffold. The combination of in vitro fluorescence recovery after photobleaching with additional fluorescence-based assays in vitro can be used to unveil mechanism, stoichiometry, and kinetic parameters of a macromolecular interaction, all of which are important for modeling protein interaction networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
116
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(122 citation statements)
references
References 31 publications
6
116
0
Order By: Relevance
“…Like Aurora B, FRAP-experiments demonstrated that all MCC-components are dynamic and cycle on and off kinetochores, suggesting that the MCC is assembled at or near kinetochores. [21][22][23][24][25][26] Consistently, subunits of APC were found to be localized at the kinetochores and along chromosome arms 60 and the spindle checkpoint machinery is required to recruit the APC/ C to kinetochores. 61 Because inactivation of the Cul3/KLHL9/KLHL13 E3-ligase leads to ectopic accumulation of active Aurora B along chromosome arms, 44 we propose a model in which Cul3/KLHL9/ KLHL13 E3-ligase maintains SAC activity by directly regulating Aurora B-mediated association of the SAC components at kinetochores (Fig.…”
Section: How Does Cul3/klhl9/klhl13 E3-ligase Maintain Sac Signaling mentioning
confidence: 82%
See 2 more Smart Citations
“…Like Aurora B, FRAP-experiments demonstrated that all MCC-components are dynamic and cycle on and off kinetochores, suggesting that the MCC is assembled at or near kinetochores. [21][22][23][24][25][26] Consistently, subunits of APC were found to be localized at the kinetochores and along chromosome arms 60 and the spindle checkpoint machinery is required to recruit the APC/ C to kinetochores. 61 Because inactivation of the Cul3/KLHL9/KLHL13 E3-ligase leads to ectopic accumulation of active Aurora B along chromosome arms, 44 we propose a model in which Cul3/KLHL9/ KLHL13 E3-ligase maintains SAC activity by directly regulating Aurora B-mediated association of the SAC components at kinetochores (Fig.…”
Section: How Does Cul3/klhl9/klhl13 E3-ligase Maintain Sac Signaling mentioning
confidence: 82%
“…14 In Xenopus egg extracts, the Aurora B-INCENP complex induces kinetochore localization of MPS1 (multipolar spindle 1), BUB1, BUB3 and CENP-E. 15 In mammalian cells, CENP-E and BUBR1 are part of a complex involved in force sensing, 16 and BUBR1, MAD2 and CENP-E are recruited to kinetochores by a mechanism that requires the kinase activity of Aurora B. [17][18][19][20] Kinetochore localization of these SAC components is dynamic, [21][22][23][24][25] similarly to the transient association of Aurora B with centromeric regions of mitotic chromosomes. 26 These results imply that the generation of the SAC-inhibitory signal might be achieved by regulated cycles of assembly and disassembly of kinetochore proteins.…”
Section: Sac Signaling At the Kinetochoresmentioning
confidence: 99%
See 1 more Smart Citation
“…Potentially, p31 comet could be up-regulated by using a two-step reaction process; however, such a scheme would have to be conceptually similar to that discussed in Model with an amplification step. We emphasize that p31 comet also could play other important roles, for example, in switching off kinetochore signaling after microtubule attachment (33). Model with an amplification step.…”
Section: Mechanisms With Diffusivementioning
confidence: 99%
“…Central to the SACnetwork is a kinetochore-bound template complex made up from Mad1 and C-Mad2. This template complex recruits O-Mad2 and stabilizes an intermediate conformation (O-Mad2*), which can bind Cdc20 efficiently and switches to closed conformation upon Cdc20-binding, tightening the connection between both with the 'safety-belt' (De Antoni et al, 2005;Luo et al, 2004;Vink et al, 2006).The CMad2:Cdc20 complex formed by this mechanism has been given the name ''template-model'' (De Antoni et al, 2005). Mad2-activation at the kinetochores is commonly seen as the central element of the SAC.…”
Section: Template Model Of Mad2-activationmentioning
confidence: 99%